Are high elevation crag lizards sensitive to climate change?. (16th January 2021) - Perold, Vonica; Ferguson, Jan Willem H.; Verburgt, Luke; Malherbe, Johan B.
Abstract: Crag lizards are restricted to montane areas where biota are strongly exposed to the effects of climate change. We investigated the factors shaping the distribution of Drakensberg crag lizards ( Pseudocordylus melanotus melanotus ; Cordylidae) by quantifying their elevational ranges, availability of shelter and prey as well as the thermal environment at three elevations. We recorded expected body temperatures using copper models of the lizards at each elevation in the field and in the laboratory, estimating the duration for which lizards must shelter from high temperatures. This correlated strongly with field observations of lizard activity during winter, spring and summer. Our models predicted that at lower elevations, lizards would shelter for longer periods each day, resulting in a marked reduction in time available for essential activities such as feeding and breeding, possibly explaining why these animals do not occur at lower elevations. The distribution and survival of these animals therefore appear to be impacted by the degree to which daytime temperatures limit their activity. Modelling future climate change scenarios at the high elevation site indicates that crag lizards would be resilient against small to moderate warming reflected by RCP4.5 climate change predictions, but populations are unlikely to persist under conditions predicted in the RCP8.5 scenario. This study is important as, unlike broader‐scope studies that cannot quantify climate change impacts on individual species, we combine detailed field data with laboratory measurements and modelling of a single species to assess the ecological constraints to which crag lizards are exposed.